1997
DOI: 10.1104/pp.114.4.1313
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cu2+ on Ion Transport Systems of the Plant Cell Plasmalemma

Abstract: Cuz+ is one of the most important micronutrients in plants. The normal growth and development of plants requires adequate Cu2+. However, the range of Cu2+ concentrations that have an appropriate effect on plants is very narrow; even a slight elevation of the upper leve1 of physiologically allowed Cu2+ concentrations leads to toxic effects in the cell resulting from disturbances in ionic homeostasis and metabolism (Loneragan et al., 1981; Robinson, 1983; Bergmann, 1992). At present the treatment of plants with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 26 publications
2
33
2
Order By: Relevance
“…First, using 86 Rb as a tracer, we confirmed that the increase in K ϩ in the medium is due to a stimulation of K ϩ efflux rather than an inhibition of K ϩ influx by copper. Unlike the copper-induced membrane depolarization reported in Nitella flexilis (Demidchik et al, 1997), in our studies no copper-induced membrane depolarization could be detected during the first 2 h under conditions similar to those used in the efflux studies. This means that short-term K ϩ efflux is electroneutral under physiological conditions.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…First, using 86 Rb as a tracer, we confirmed that the increase in K ϩ in the medium is due to a stimulation of K ϩ efflux rather than an inhibition of K ϩ influx by copper. Unlike the copper-induced membrane depolarization reported in Nitella flexilis (Demidchik et al, 1997), in our studies no copper-induced membrane depolarization could be detected during the first 2 h under conditions similar to those used in the efflux studies. This means that short-term K ϩ efflux is electroneutral under physiological conditions.…”
Section: Discussioncontrasting
confidence: 49%
“…Such oxidative damage might disrupt membranes, resulting in nonspecific K ϩ leakage out of the cell. Recent electrophysiological studies with the giant algal internode cells of Nitella flexilis have indicated that copper has four effects on the plasma membrane: (a) it increases the nonselective conductance; (b) it inhibits Cl Ϫ channels; (c) it inhibits the plasma membrane H ϩ -ATPase; and (d) it promotes lipid peroxidation (Demidchik et al, 1997). Since Ca 2ϩ could prevent the increase in nonspecific conductance, copper appeared to be competing with Ca 2ϩ for binding sites on the membrane.…”
mentioning
confidence: 99%
“…It has been proven that the Cuinduced changes in cell permeability can be attributed to nonselective conductance increases. 35 In addition, excessive Cu can damage root cell membrane and the root exclusion mechanisms collapse, 35,36 thereby disrupting ion channel absorption regulation. 36 It is therefore hypothesized that solutes might be indiscriminately taken up by the defective roots, damaged by either excess Cu or hot water, with unconventional regulation of ion channels and then translocated to shoots.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To date, data concerning the action of heavy metals on plasma membrane H + -ATPase are limited. A few observations have indicated that enzyme activity was changed under heavy metal (Cd, Cu, Ni, Al) stresses (Lindberg & Wingstrand, 1985;Kennedy and Gonsalves, 1989;Ros et al, 1992 a,b;Fodor et al, 1995;Demidchik et al, 1997;Astolfi et al, 2003;Burzyński & Kolano, 2003;Astolfi et al, 2005;Shen et al, 2005;Janicka-Russak et al, 2008;Kabała et al, 2008). The effect of metals on plasma membrane H + -ATPase activity depends on time of exposure of plants to heavy metals, kind and concentration of heavy metal or plant species.…”
Section: Heavy Metalsmentioning
confidence: 99%